Acute myeloid leukemia with KMT2A-SEPT5 translocation: A case report and review of the literature. (3rd January 2018) - Elzamly, Shaimaa; Chavali, Santosh; Tonk, Vijay; Tonk, Sahil; Gaur, Sumit; Tarango, Darlene; Torabi, Alireza
Chromosomal rearrangement involving the KMT2A gene is one of the most common genetic alteration in acute myeloid leukemia. A total of 135 different KMT2A rearrangements have been identified, where 94 translocation partner genes are now characterized at the molecular level. Of these 94 translocation partner genes, 35 translocation partner genes occur recurrently, but only 9 specific gene fusions account for more than 90% of cases. Translocation of KMT2A with SEPT5 gene at 22q11.2 is rare, with few reported cases in the literature. In this report, we are presenting a case of KMT2A-SEPT5 fusion in de novo acute myeloid leukemia with t(11;22)(q23;q11.2) with a review of the literature.